Online Gender Based Violence Against Women - Ratu Indra Kasih Pratiwi; Hijrah Adhyanti Mirzana; Audyna Mayasari Muin (Journal of Development Research, 2023)
This study aims to analyze the regulation of online gender based violence against women in Indonesia criminal regulations. This research use the normative methods. Accumulation method used by the author in this research is literature study. With a research approach that prioritizes legal materials in the form of legislation as a basic reference material in conducting research. As well as a conceptual approach used to understand concepts related to normalization in a legislation whether on accordance with the spirit contained in the underlying legal concepted. The research’s result shown that the regulation of online gender based violence against women in Indonesia criminal law could be concluded as follow: first, Law Number 1 of 1946 on Criminal Regulations. Second, Law Number 19 of 2016 on amendment to Law Number 11 of 2008 on Information and Electronic Transaction. Third, Law Number 44 of 2008 on Pornography, and last Law Number 12 of 2022 on Crime of Sexual Violence.